A Ca²⁺-activated proteinase in chicken skeletal muscle - Smith, Arlene Atkinson (Division of Medical Biochemistry and Structural Biology, 2018)
A neutral calcium-activated protease of muscle (CAP) has previously been characterised and may play a role in myofibrillar disassembly and turnover. In this study both CAP and endogenous CAP inhibitor from adult and embryonic chicken skeletal muscle have been partially purified by DEAE-cellulose and Sephadex G-150 chromatography. CAP from embryonic muscle shows similar properties to the corresponding enzyme from adult tissue with respect to calcium dependence (maximum activity at 1.0 rnM Ca²⁺), pH optimum (7.2) and sensitivity to proteinase inhibitors (inhibited by leupeptin and chymostatin). Both embryonic and adult enzymes were found to have molecular weights of 112000 daltons by gel filtration on Sephadex G-150. CAP activity was present in cultured skeletal muscle cells and increased with cellular growth and differentiation (five-fold). The presence of an inhibitor of CAP was demonstrated in cell cultures by ion-exchange chromatography, the levels of which decreased with a simultaneous increase in CAP activity. CAP activity showed an increase in developing muscle from 12-day embryos to 7-week chicks in relation to cellular DNA (3.8- fold), although the extent of this increase did not match the extent of accumulation of myofibrillar proteins. High levels of CAP inhibitor were found in early embryonic muscle and these decreased markedly during development. CAP inhibitor from embryonic tissue was fractionated into 3 species using DEAE-cellulose in contrast to inhibitor from adult tissue which exhibited only two species. The results indicate that the levels of CAP greatly increase at a time when myofibrillar content of muscle is rapidly increasing and, in addition, demonstrate that CAP activity may be controlled to a large extent by the levels of an intracellular inhibitor.